Disruption of the ascending arousal system and cortical attention networks in post-stroke delirium and spatial neglect. (December 2017) - Boukrina, Olga; Barrett, A.M.
Graphical abstract: Highlights: Delirium is an acute attention and cognitive dysfunction hindering stroke recovery. Rate of delirium is increased in right-brain stroke and patients with spatial neglect. Common brain circuitry disrupted in delirium and spatial neglect is reviewed. The ascending reticular-thalamocortical arousal system plays a role in both disorders. The right-dominant cortico-limbic spatial attention system may also be affected. Abstract: Delirium is an acute attention and cognitive dysfunction, adversely affecting functional outcomes and mortality. As many as half of hospitalized right brain stroke survivors may develop delirium. Further, about 50% of right stroke patients experience spatial neglect, impairing safety and recovery. In this review we explore the brain mechanisms, which may explain the high incidence of delirium and spatial neglect after right-brain stroke. We suggest that brain networks for spatial attention and arousal, composed of ascending projections from the midbrain nuclei and integrating dorsal and ventral cortical and limbic components, may underlie impairments in delirium and spatial neglect. We propose that lateralized deficits in spatial neglect may arise because cortical and limbic components of these functional networks are disproportionally impaired by right-brain strokes, and that spatial neglect may lower the threshold for developing delirium. An improved understanding of the brain basis of delirium and spatial neglect could provide a critical biomarker for initiating preventive care in stroke patients at high risk of hospital morbidity and loss of independence.